2016
DOI: 10.1371/journal.pmed.1001904
|View full text |Cite
|
Sign up to set email alerts
|

“Real-Time” Monitoring of Under-Five Mortality: Lessons for Strengthened Vital Statistics Systems

Abstract: Bryce and colleagues, reflect on lessons that can be learned from the Real-Time Monitoring of Under-Five Mortality Collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In addition to controls and checks programmed in the CAPI system, careful training and field supervision of interviewers were used to try to minimize errors known to occur during the collection of FPH data, e.g., errors in age and date declaration, misclassifications of stillbirths as neonatal deaths (and vice-versa), and omission of births and deaths [ 9 , 10 , 25 , 26 ]. As mentioned elsewhere [ 14 ], there were initial concerns about the quality of the FPH data collected in Ghana. In this paper, we thus report extensive analyses of potential errors and inconsistencies in such data (see below).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to controls and checks programmed in the CAPI system, careful training and field supervision of interviewers were used to try to minimize errors known to occur during the collection of FPH data, e.g., errors in age and date declaration, misclassifications of stillbirths as neonatal deaths (and vice-versa), and omission of births and deaths [ 9 , 10 , 25 , 26 ]. As mentioned elsewhere [ 14 ], there were initial concerns about the quality of the FPH data collected in Ghana. In this paper, we thus report extensive analyses of potential errors and inconsistencies in such data (see below).…”
Section: Methodsmentioning
confidence: 99%
“…RMM methods included: community-based reporting on vital events, various adjustments to HMIS data, as well as rapid household survey methods (e.g., summary birth histories). They were tested in several Sub-Saharan African countries [ 14 ], with heterogeneous results [ 15 ]. In Ethiopia and Malawi, for example, community-based reports of vital events collected by paid workers under-estimated mortality levels compared to survey data [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The scope of this study is limited for several reasons. First, results are based on age profiles constructed using full-life histories from survey data, which are subject to several sources of error; rather than high quality vital registration systems, which are inexistent or deficient in the countries included in our study (Bryce et al 2016). Second, we used different measures of inequality to improve the robustness of our analysis as they differ in their underlying properties and sensitivity to age-specific mortality change (van Raalte and Caswell 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study should be judge in light of several limitations. First, the gold standard for the analysis of mortality in more developed countries relies on the existence of high quality vital registration systems, but those systems are inexistent or deficient in the countries included in our study (50). Second, this study relies on self-reported information from life histories available in nationally-representative surveys, which are subject to several sources of error.…”
Section: Discussionmentioning
confidence: 99%